2021
DOI: 10.1080/10412905.2021.1925362
|View full text |Cite
|
Sign up to set email alerts
|

Determining the authenticity of methyl salicylate in Gaultheria procumbens L. and Betula lenta L. essential oils using isotope ratio mass spectrometry

Abstract: The essential oils of wintergreen and birch are composed primarily of methyl salicylate. Because this compound can easily be synthesized, wintergreen and birch oils are frequently adulterated. By using Gas chromatography-combustion/pyrolysis-isotope ratio mass spectrometry (GC-C/P-IRMS) in conjunction with TC/EA-IRMS, GC-FID, GC-MS, and 14 C radiocarbon dating, criteria will be established that can be used to distinguish authentic and natural wintergreen and birch essential oils from adulterated ones or from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Emissions of MeSA and TMTT were observed in the sampled tomato plants. Both compounds have been associated with plant physiological stress (Rose et al, 1996;Kant et al, 2004), although some plants, for example, wintergreen (Gaultheria procumbens L.) and sweet birch (Betula lenta L.) are known to store MeSA in their essential oils (Murphy et al, 2021). Sixteen out of the 18 sampled tomato plants (i.e., all except for Summer Set 1 and Black Cherry 1) were emitting detectable amounts of MeSA at ambient temperatures (25 C/30 C) prior to the heat treatment (Figures 4 and 5), while all but one of the plants were emitting some amount of TMTT (Figure 1).…”
Section: Emission Of Stress Compoundsmentioning
confidence: 99%
“…Emissions of MeSA and TMTT were observed in the sampled tomato plants. Both compounds have been associated with plant physiological stress (Rose et al, 1996;Kant et al, 2004), although some plants, for example, wintergreen (Gaultheria procumbens L.) and sweet birch (Betula lenta L.) are known to store MeSA in their essential oils (Murphy et al, 2021). Sixteen out of the 18 sampled tomato plants (i.e., all except for Summer Set 1 and Black Cherry 1) were emitting detectable amounts of MeSA at ambient temperatures (25 C/30 C) prior to the heat treatment (Figures 4 and 5), while all but one of the plants were emitting some amount of TMTT (Figure 1).…”
Section: Emission Of Stress Compoundsmentioning
confidence: 99%
“…Given the variability of essential oil profiles and the prohibitive costs of natural products, essential oils containing ( E )-anethol are often adulterated with lower-priced natural or synthetically produced alternatives [ 3 , 24 , 25 , 26 ]. To ensure the authentication of natural compounds, gas chromatography/mass spectrometry (GC/MS) and gas chromatography/isotope ratio mass spectrometry (GC/IRMS), among other analytical techniques, have been reported as powerful analytical tools [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. These same researchers have reported that identification of specific marker compounds by GC/MS and stable isotope analysis of prominent compounds assists in detecting adulteration with synthetic compounds and/or distinguishing natural compounds based on the origin of plant species, chemotype, and provenance.…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotope ratios, δ 2 H and δ13 C, for (E)-anethol prominent commercially available samples (n = 30): anise(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), star anise(27)(28)(29)(30)(31)(32)(33)(34), and fennel (40-50). Samples were analyzed in triplicate to ensure repeatability (δ 2 H values are reported with a standard deviation ≤ 2.0‰ and δ13 C values are reported with a standard deviation ≤ 0.2‰).…”
mentioning
confidence: 99%
“…Cinnamon bark oil is commonly substituted with the less costly cinnamon leaf oil . Wintergreen and birch oils are known to be adulterated with synthetic methyl salicylate. This type of adulteration is most commonly detected using a number of stable isotope ratio (e.g., 2 H/ 1 H, 13 C/ 12 C, or 18 O/ 16 O) measurements …”
Section: Introductionmentioning
confidence: 99%